2014
DOI: 10.7202/1026878ar
|View full text |Cite
|
Sign up to set email alerts
|

Réduction des risques et jeux d’argent. Questions ouvertes par la révision du dispositif suisse

Abstract: Initialement associé à l’approche de santé publique des drogues illégales, le concept de réduction des risques et dommages (RDR) a été défini par des programmes et des pratiques visant à réduire les conséquences négatives des conduites addictives sur les plans sanitaire, social et économique, et ce, sur la base d’indicateurs scientifiquement pertinents. En matière de jeu excessif, l’approche de santé publique demeure le parent pauvre et le concept de RDR n’a été implanté que de manière marginale, subordonnée à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, consideration of problem gambling as a public health issue is only recent [23]. Since the implementation of a gambling policy, specialized prevention and treatment centres have been created in most Swiss cantons [26].…”
Section: Treatment Availability In Switzerlandmentioning
confidence: 99%
“…However, consideration of problem gambling as a public health issue is only recent [23]. Since the implementation of a gambling policy, specialized prevention and treatment centres have been created in most Swiss cantons [26].…”
Section: Treatment Availability In Switzerlandmentioning
confidence: 99%
“…Three studies address the TC on gambling across jurisdictions [2,41,42]. Two of these [2,41] found little difference between regimes regarding TC, but the study by Gu [42] [45] compared TC on gambling in Switzerland between the licensed casino market and the monopolistic lottery market. Despite these differing products, the study found that both monopolistic and licensed operators operated in an expansionist manner looking to expand markets and TC.…”
Section: Total Consumptionmentioning
confidence: 99%